"It's Not Gonna Leave Any Scars": Trauma and Coping Among Execution Team Members. (September 2021) - Chiappetta, Casey; Johnson, Robert
A trauma framework is applied to the experiences of execution team members. A directed content analysis of three seminal publications is used to investigate how execution team members respond to observing and participating in executions, a potentially traumatic stressor. Through these texts, supplemented by other research, the study finds that the execution process, meant to facilitate executions and insulate execution team officers from stress, only partially achieves these goals. The findings suggest that many of the concepts central to understanding executioners at work—how they understand and cope with their roles—are dynamic rather than static and vary in degree across persons and situations. Execution team officers report varying degrees of difficulty fully rationalizing and diffusing responsibility for their actions, ultimately leading to internal conflict and stress about the death penalty and participation in executions.